(untitled) (Circe de clásicos y modernos, 2018)
Terence’s comedy The Brothershas been interpreted by the criticism in many different ways. Some scholars argue that Micio is a uniform character, while others consider him inconsistent and changing. The goal of this article is to show that Micio is coherent throughout the comedy and that this work of Terence must be understood more as a conflict of characters than as the opposition of two educational systems.